Nature Fun Learning in Early Childhood Education based on Nature (In The Bulukerto Nature Play Group) - Kuswanto, Kuswanto; Wulansari, Betty Yulia; Muttaqin, Muhammad Azam (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2024)
Nature-based early childhood education (PAUD) is currently one of the trend centers for educational institutions. Nature-based PAUD is PAUD whose learning uses nature as a learning resource, learning media and outdoor play area. KB Alam Bulukerto is one of the nature-based PAUDs in Wonogiri Regency. This KB is one of the favorite KBs with the advantage of Nature Fun Learning. Nature Fun Learning is a natural activity typical of the Alam Bulukerto Play Group (KB) which needs to be researched in order to spread good practice in its activities. This research method uses qualitative descriptive research with the research subjects being principals, teachers, students and guardians of KB Alam Bulukerto. The aim of this research is to examine good practices of Nature Fun Learning at KB Alam Bulukerto. The results of this research found good practices in Nature Fun Learning activities in the form of (1) Nature Walk, (2) Gardening, and (3) Raising.Â Â